Factors Changing the Gayo Ethnic’s Traditional Marriage Procession in Lut Tawar Sub-District of Takengon, Central Aceh, Indonesia - Auni, Luthfi; Manan, Abdul; Abubakar, Al Yasa' (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2022)
The Gayo ethnic has diverse and unique customs compared to their family ethics in Aceh, one of which is its indigenous marriage pattern, procession, stage, and philosophy in that tradition. This study is qualitative research using an anthropological approach. Data collection techniques used are interviews and documentation and observation studies. The results of the study show that there have been changes in Gayo society which have resulted in different traditions and rituals and have adapted very much to the present. The community now tends to adapt the series of processions and phases of marriage traditions as to fit their socio-cultural atmosphere today which is now part of Gayo ethnic life atmosphere. This has brought value shift and change when explored from all aspects of its implementation. As a result, the philosophies of the indigenous marriage pattern and its series of sacred and ritual processions in every phase which was full of valuable messages and meanings including some traditional authoritative actors that are involved within become faded, forgotten, and even eliminated. The poor knowledge of the young Gayo people about their traditional values as their ancestor's cultural heritage shifted their attitudes and mindsets. The findings show that the direction of various changes within a series of Gayo marriage processions and phases pivots and leads to the concept of modern and global culture as the results of the changing of attitude, mindset and willingness to change within the community, cultural acculturation, the crisis of tradition information sources as due to the retreat of traditional leaders who played role in transmitting their culture and tradition; and the emergence of various channel and agents of changes such as the government and religious institutions, the rising level of education, people mobility, assimilation through mixed marriages, tourist destinations and mass media and new technologies as parts of agents of changes.